ANALYSIS OF MARKET OPPORTUNITIES FOR RASPBERRY PRODUCTION IN THE REPUBLIC OF NORTH MACEDONIA - Bojkovska, Katerina; Jankulovski, Nikolce; Mihajlovski, Goran; Momirceski, Jovica (International Journal of Research -GRANTHAALAYAH, 2020)
The purpose of the research in this paper is to analyze the production of raspberries in Republic of N. Macedonia and to perceive its place on the world market of raspberries, as well as to analyze the market opportunities for raspberry production in Republic of N. Macedonia. The results of the research show that Russia occupies 19% of world raspberry production for 2018 while Mexico occupies 15% of total raspberry production and Serbia occupies 15% of total raspberry production for 2018, i.e. it is the third largest producer in the world. The production of raspberries worldwide has increased by 7% in 2018 compared to 2017, while compared to 2010 this production worldwide has increased by 40%. Republic of N. Macedonia with its 33rd place occupies 0.03% of the total world production of raspberries in 2018 from a total of 45 countries. But despite the small share in world raspberry production in 2018, Republic of N. Macedonia records a drastic increase (by 96%) compared to 2010, while compared to 2017 it increased by 25%. Republic of N. Macedonia has the necessary conditions for the production of raspberries, but still this branch is not fully developed.